2014
DOI: 10.1289/ehp.1307984
|View full text |Cite
|
Sign up to set email alerts
|

Early Postnatal Exposure to Ultrafine Particulate Matter Air Pollution: Persistent Ventriculomegaly, Neurochemical Disruption, and Glial Activation Preferentially in Male Mice

Abstract: Background: Air pollution has been associated with adverse neurological and behavioral health effects in children and adults. Recent studies link air pollutant exposure to adverse neurodevelopmental outcomes, including increased risk for autism, cognitive decline, ischemic stroke, schizophrenia, and depression.Objectives: We sought to investigate the mechanism(s) by which exposure to ultrafine concentrated ambient particles (CAPs) adversely influences central nervous system (CNS) development.Methods: We expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
174
3
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(202 citation statements)
references
References 59 publications
18
174
3
7
Order By: Relevance
“…As previously reported [80], mean particle diameter for these exposures was consistently below 100 nm; mean CAPS counts across the 8 days of exposures was approximately 200,000 particles/cm 3 , and the mean particle mass concentration was 96 μg/m 3 . These values are similar to values reported for expressway traffic in L. A.…”
Section: Methodssupporting
confidence: 81%
“…As previously reported [80], mean particle diameter for these exposures was consistently below 100 nm; mean CAPS counts across the 8 days of exposures was approximately 200,000 particles/cm 3 , and the mean particle mass concentration was 96 μg/m 3 . These values are similar to values reported for expressway traffic in L. A.…”
Section: Methodssupporting
confidence: 81%
“…In the present study, PM 2.5 exposure did not induce marked changes in GFAP in male rat brain. The findings in this study differ from those of Allen et al (2014) with respect to GFAP expression, possibly due to factors such as age, experimental PM administration, and species. Lucchini et al (2012) demonstrated that children were more sensitive to PM than adults, which may account for the findings noted by Allen et al (2014).…”
Section: Discussioncontrasting
confidence: 98%
“…One of the prominent pathological features of IS is reactive astrocytes, characterized by changes in morphology and upregulation of GFAP, and finally forming glial scars (Choudhury and Ding, 2015). Allen et al (2014) reported that early postnatal exposure to inhalation PM 2.5 at 10-fold the concentration in ambient air in male C57BL6/J mice decreased GFAP immunoreaction at postnatal day (PND) 14 and PND 55, whereas an increased GFAP expression was noted at PND14 in the female mouse brain. In the present study, PM 2.5 exposure did not induce marked changes in GFAP in male rat brain.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that air pollution may have a neurotoxic effect at early stages of development (Genc et al, 2012) even in newborns with appropriate fetal growth. Neuroinflammation, oxidative stress, and glial activation have been identified as potential mechanisms by which air pollution may impair the central nervous system (Calderón-Garcidueñas et al, 2012;Block and Calderón-Garcidueñas, 2009;Allen et al, 2014). Neuroinflammation prompted by a fetal inflammatory response syndrome can damage the fetal brain and increase the risk of ventriculomegaly in fetuses and newborns (Korzeniewski et al, 2014), itself associated with larger HC and total brain volume during pregnancy (Roza et al, 2008).…”
Section: Discussionmentioning
confidence: 99%